Exploring changes on science teachers' conceptions about professional development - Sağlam Karaçal, Sezin. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
The purpose of this qualitative case study was to explore changes on science teachers’ conceptions about professional development. How teachers’ perceptions, ex periences, and approaches about their professional development background, and plans for the future have been changed through the time of eight years were explored. The ﬁrst phase of the study was conducted in the 2010-2011 educational year with 14 pri vate school teachers. Data were collected with semi-structured interviews and analyzed using constant comparative method. After the open, axial and selective coding, four main themes (a) identity, (b) department, (c) school context and (d) national con text, emerged that described teachers’ conceptions about professional development. The second phase of the study was conducted in 2019 with three teachers purpose fully selected among the participants of the ﬁrst phase. Interview questions for the second phase were revised based on the four themes from the ﬁrst phase. After the teachers were individually interviewed, the data gathered were analyzed in the light of themes which arose from the ﬁrst phase. The results showed important changes in teachers’ conceptions about professional development. Conclusions and implications of the ﬁndings are discussed.
Keywords: Science teachers.